2021
DOI: 10.1073/pnas.2103021118
|View full text |Cite
|
Sign up to set email alerts
|

Toll9 fromBombyx morifunctions as a pattern recognition receptor that shares features with Toll-like receptor 4 from mammals

Abstract: Toll/Toll-like receptors (TLRs) are key regulators of the innate immune system in both invertebrates and vertebrates. However, while mammalian TLRs directly recognize pathogen-associated molecular patterns, the insect Toll pathway is thought to be primarily activated by binding Spätzle cytokines that are processed from inactive precursors in response to microbial infection. Phylogenetic and structural data generated in this study supported earlier results showing that Toll9 members differ from other insect Tol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 53 publications
(71 reference statements)
0
26
0
Order By: Relevance
“…In contrast, in B. mori , LPS from gram-negative infection can activate the expression of AMPs such as cecropin B, whereas in mammals, TLR4 requires MD-2 for LPS recognition in response to gram-negative infections ( 20 , 27 ). Recently, B. mori Toll9 was found to colocalize with BmMD-2A and BmMD-2B on the surface of B. mori immune tissues ( 21 ). Simulated structures of B. mori MD-2A–lipid A and ML-2B–lipid A complexes based on the structure of the human MD2–lipid A complex revealed that similar to human MD-2, BmMD-2A and BmMD-2B contain two antiparallel β-sheets and a deep hydrophobic cavity.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, in B. mori , LPS from gram-negative infection can activate the expression of AMPs such as cecropin B, whereas in mammals, TLR4 requires MD-2 for LPS recognition in response to gram-negative infections ( 20 , 27 ). Recently, B. mori Toll9 was found to colocalize with BmMD-2A and BmMD-2B on the surface of B. mori immune tissues ( 21 ). Simulated structures of B. mori MD-2A–lipid A and ML-2B–lipid A complexes based on the structure of the human MD2–lipid A complex revealed that similar to human MD-2, BmMD-2A and BmMD-2B contain two antiparallel β-sheets and a deep hydrophobic cavity.…”
Section: Discussionmentioning
confidence: 99%
“…The hydrophobic acyl chains of lipid A can bind to the human MD-2/LPS complex in this cavity, albeit in different directions, implying that B. mori MD-2–like proteins are the accessary proteins required for LPS recognition ( 20 ). Similar to mammalian TLR4 ectodomains, the homology-modeled structure of B. mori Toll9 using human TLR4 as a template contains a cysteine cluster carboxyl terminus to the leucine-rich repeats, with a characteristic horseshoe-like shape, suggesting that insect Toll9 evolutionarily clusters with mammalian TLR4 ( 21 ). The LPS recognition and signaling functions of the Toll9/MD-2–like protein complex of B. mori may be similar to that of the mammalian TLR4/MD-2 complex ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations